Fsc Part 1 Mathematics (Complete Solution)

Q2
Use matrices to solve the following systems

(i)  
x-2y+z = -1
3x+y-2z = 4
y-z = 1
}

SOLUTION:

The matrix form of the system

   
 
1 -2 1
3 1 -2
0 1 -1
 
  
 
x
y
z
 
   =  
 
-1
4
1
 
 Let   A=
 
1 -2 1
3 1 -2
0 1 -1
 
 ; X=
 
x
y
z
 
 ;    B= 
 
-1
4
1
 

then system becomes  AX=B

=> X=A-1B

lAl= 
 
1 -2 1
1 -2
0 1 -1
 

=1(-1+2)+2(-3+0)+1(3-0)

=1-6+3

=-5+3

=-2

 Cofactors of A =  
 
A11 A12 A13
A21 A22 A23
A31 A32 A33
 

Aij=(-1)i+jMij

A11  =  (-1)1+1
 
1 -2
1 -1
 
 =(-1)2 (-1+2) =1
A12  =  (-1)1+2
 
3 -2
0 -1
 
 =(-1)3 (-3+2) =3
A13  =  (-1)1+3
 
3 1
0 1
 
 =(-1)4 (3-0) =3
A21  =  (-1)2+1
 
-2 1
1 -1
 
 =(-1)3 (2-1) =-1
A22  =  (-1)2+2
 
1 1
0 -1
 
 =(-1)4 (-1-0) =-1
A23  =  (-1)2+3
 
1 -2
0 1
 
 =(-1)5 (1+0) =-1
A31  =  (-1)3+1
 
-2 1
1 -2
 
 =(-1)4 (4-1) =3
A32  =  (-1)3+2
 
1 1
3 -2
 
 =(-1)5 (-2-3) =5
A33  =  (-1)3+3
 
1 -2
3 1
 
 =(-1)6 (1+6) =7
 Cofactors of A =  
 
1 3 3
-1 -1 -1
3 5 7
 
    Adj.A=(Cofactors of A)t=
 
1 -1 3
3 -1 5
3 -1 7
 
SO,  A-1=
Adj.A
lAl
=
1
-2
 
1 -1 3
3 -1 5
3 -1 7
 
=
 
-1/2 1/2 -3/2
-3/2 -1/2 -5/2
-3/2 1/2 -7/2
 

then X=A-1B

  X= A-1B=
 
-1/2 1/2 -3/2
-3/2 -1/2 -5/2
-3/2 1/2 -7/2
 
  
 
-1
4
1
 
 
 
x
y
z
 
=  
 
1
1
0
 

x=1   , y=1  , z=0


(ii)
2x1+x2+3x3 = 3
x1+x2-2x3 = 0
-3x1-x2+2x3 = -4
}

SOLUTION:

The matrix form of the system

   
 
2 1 3
1 1 -2
-3 -1 2
 
  
 
x1
x2
x3
 
   =  
 
-3
0
-4
 
 Let   A=
 
2 1 2
1 1 -2
-3 -1 2
 
 ; X=
 
x1
x2
x3
 
 ;    B= 
 
-3
0
-4
 

then system becomes  AX=B

=> X=A-1B

lAl= 
 
1 3
1 1 -2
-3 -1 2
 

=2(2-2)-1(2-5)+3(-1+3)

=0+4+6

=4+6

=10

 Cofactors of A =  
 
A11 A12 A13
A21 A22 A23
A31 A32 A33
 

Aij=(-1)i+jMij

A11  =  (-1)1+1
 
1 -2
-1 2
 
 =(-1)2 (2-2) =0
A12  =  (-1)1+2
 
-1 2
3 -2
 
 =(-1)3 (2-6) =4
A13  =  (-1)1+3
 
1 1
-3 -1
 
 =(-1)4 (-1+3) =2
A21  =  (-1)2+1
 
-1 -3
1 -2
 
 =(-1)3 (2+3) =-5
A22  =  (-1)2+2
 
2 3
-3 2
 
 =(-1)4 (4+9) =13
A23  =  (-1)2+3
 
-2 -1
3 1
 
 =(-1)5 (-2+3) =-1
A31  =  (-1)3+1
 
1 3
1 -2
 
 =(-1)4 (-2-3) =-5
A32  =  (-1)3+2
 
-2 -3
-1 2
 
 =(-1)5 (-4-3) =7
A33  =  (-1)3+3
 
2 1
1 1
 
 =(-1)6 (2-1) =1
 Cofactors of A =  
 
0 4 2
-5 13 -1
-5 7 1
 
    Adj.A=(Cofactors of A)t=
 
0 -5 -5
4 13 7
2 -1 1
 
SO,  A-1=
Adj.A
lAl
=
1
10
 
0 -5 -5
4 13 7
2 -1 1
 
=
 
0 -1/2 -1/2
2/5 13/10 7/10
1/5 -1/10 1/10
 

then X=A-1B

  X= A-1B=
 
0 -1/2 -1/2
2/5 13/10 7/10
1/5 -1/10 1/10
 
  
 
-3
0
-4
 
 
 
x1
x2
x3
 
=  
 
2
-4
-1
 

x1=2   , x2= -4  , x3= -1


(iii)  
x+y = 2
2x-z = 1
2y-3z = -1
}

SOLUTION:

The matrix form of the system

   
 
1 1 0
2 0 -1
0 2 -3
 
  
 
x
y
z
 
   =  
 
2
1
-1
 
 Let   A=
 
1 1 0
2 0 -1
0 2 -3
 
 ; X=
 
x
y
z
 
 ;    B= 
 
2
1
-1
 

then system becomes  AX=B

=> X=A-1B

lAl= 
 
1 1 0
2 0 -1
0 2 -3
 

=1(0+2)-1(-6+0)+0(4-0)

=2+6+0

=2+6

=8

 Cofactors of A =  
 
A11 A12 A13
A21 A22 A23
A31 A32 A33
 

Aij=(-1)i+jMij

A11  =  (-1)1+1
 
0 -1
2 -3
 
 =(-1)2 (0+2) =2
A12  =  (-1)1+2
 
2 -1
0 -3
 
 =(-1)3 (-6+0) =6
A13  =  (-1)1+3
 
2 0
0 2
 
 =(-1)4 (4-0) =4
A21  =  (-1)2+1
 
1 0
2 -3
 
 =(-1)3 (-3-0) =3
A22  =  (-1)2+2
 
1 0
0 -3
 
 =(-1)4 (-3-0) = -3
A23  =  (-1)2+3
 
1 1
0 2
 
 =(-1)5 (2-0) =-2
A31  =  (-1)3+1
 
1 1
0 -1
 
 =(-1)4 (-1-0) =-1
A32  =  (-1)3+2
 
1 0
2 -1
 
 =(-1)5 (-1-0) =1
A33  =  (-1)3+3
 
1 1
2 0
 
 =(-1)6 (0-2) =-2
 Cofactors of A =  
 
2 6 4
3 -3 -2
-1 1 -2
 
    Adj.A=(Cofactors of A)t=
 
2 3 -1
6 -3 1
4 -2 -2
 
SO,  A-1=
Adj.A
lAl
=
1
8
 
2 3 -1
6 -3 1
4 -2 -2
 
=
 
2/8 3/8 -1/8
6/8 -3/8 1/8
4/8 -2/8 -2/8
 

then X=A-1B

  X= A-1B=
 
2/8 3/8 -1/8
6/8 -3/8 1/8
4/8 -2/8 -2/8
 
  
 
1
-1
 
 
 
x
y
z
 
=  
 
1
1
1
 

x=1  , y=1  , z=1       ANSWER

Other Topics

;